WDR45, one gene associated with multiple neurodevelopmental disorders. Issue 12 (2nd December 2021) - Cong, Yingying; So, Vincent; Tijssen, Marina A. J.; Verbeek, Dineke S.; Reggiori, Fulvio; Mauthe, Mario
ABSTRACT: The WDR45 gene is localized on the X-chromosome and variants in this gene are linked to six different neurodegenerative disorders, i.e., ß-propeller protein associated neurodegeneration, Rett-like syndrome, intellectual disability, and epileptic encephalopathies including developmental and epileptic encephalopathy, early-onset epileptic encephalopathy and West syndrome and potentially also specific malignancies. WDR45/WIPI4 is a WD-repeat β-propeller protein that belongs to the WIPI (WD repeat domain, phosphoinositide interacting) family. The precise cellular function of WDR45 is still largely unknown, but deletions or conventional variants in WDR45 can lead to macroautophagy/autophagy defects, malfunctioning mitochondria, endoplasmic reticulum stress and unbalanced iron homeostasis, suggesting that this protein functions in one or more pathways regulating directly or indirectly those processes. As a result, the underlying cause of the WDR45-associated disorders remains unknown. In this review, we summarize the current knowledge about the cellular and physiological functions of WDR45 and highlight how genetic variants in its encoding gene may contribute to the pathophysiology of the associated diseases. In particular, we connect clinical manifestations of the disorders with their potential cellular origin of malfunctioning and critically discuss whether it is possible that one of the most prominent shared features, i.e., brain iron accumulation, is the primary cause for those disorders. Abbreviations: ATG/Atg: autophagy related; BPAN: ß-propeller protein associated neurodegeneration; CNS: central nervous system; DEE: developmental and epileptic encephalopathy; EEG: electroencephalograph; ENO2/neuron-specific enolase, enolase 2; EOEE: early-onset epileptic encephalopathy; ER: endoplasmic reticulum; ID: intellectual disability; IDR: intrinsically disordered region; MRI: magnetic resonance imaging; NBIA: neurodegeneration with brain iron accumulation; NCOA4: nuclear receptor coactivator 4; PtdIns3P: phosphatidylinositol-3-phosphate; RLS: Rett-like syndrome; WDR45: WD repeat domain 45; WIPI: WD repeat domain, phosphoinositide interacting